Forging Progress: Scientists and Engineers Shaping the Dutch East Indies Transformation, 1778-1942 - Machmudi, Yon; Abdurakhman, Abdurakhman; Fauzi, Wildan Insan (History Department, Semarang State University and Historian Society of Indonesia, 2024)
European students started arriving in the Dutch East Indies in the 18th century. Later in the 20th century, the Dutch began implementing various technologies in irrigation, roads, railways, shipping, and industry. Colonial politics gave scientists and engineers an important and strategic place in the Dutch East Indies government. The central question guiding this research is, “What role did scientists and engineers play in the modernization of the Dutch East Indies from 1778 to 1942?”. This historical research uses various archives at ANRI and newspapers from the colonial era to explore the role of scientists and engineers in developing science and technology and the transformation of the Dutch East Indies. The development of science and technology in the Dutch East Indies was intricately linked to Dutch colonial politics, disease outbreaks, capitalism’s growth, and modernization. The findings of this research show the role of engineers in various projects for the construction of irrigation canals, ports, dams, roads, railways, trams, mines, telegraphs, airplanes, weapons, industry, and radio. These various projects impacted community mobility, city development, provision of clothing and food, employment opportunities, and other socio-economic impacts. Dutch scientists’ activities initially had a limited impact on colonial society due to their elitist nature, lack of social support, bureaucratic obstacles, and entanglements in the political sphere. Dutch scientists have important positions in various research institutions, including botany, archaeology, physics, and the chemical industry. Pelajar Eropa mulai berdatangan ke Hindia Belanda pada abad ke-18. Kemudian pada abad ke-20, Belanda mulai menerapkan berbagai teknologi di bidang irigasi, jalan raya, kereta api, pelayaran, dan industri. Politik kolonial memberikan kedudukan penting dan strategis bagi para ilmuwan dan insinyur dalam pemerintahan Hindia Belanda. Pertanyaan sentral yang memandu penelitian ini adalah, “Apa peran ilmuwan dan insinyur dalam modernisasi Hindia Belanda pada tahun 1778 hingga 1942?”. Penelitian sejarah ini menggunakan berbagai arsip di ANRI dan surat kabar masa kolonial untuk menggali peran ilmuwan dan insinyur dalam pengembangan ilmu pengetahuan dan teknologi serta transformasi Hindia Belanda. Perkembangan ilmu pengetahuan dan teknologi di Hindia Belanda erat kaitannya dengan politik kolonial Belanda, wabah penyakit, pertumbuhan kapitalisme, dan modernisasi. Temuan penelitian ini menunjukkan peran insinyur dalam berbagai proyek pembangunan saluran irigasi, pelabuhan, bendungan, jalan raya, kereta api, trem, pertambangan, telegraf, pesawat terbang, senjata, industri, dan radio. Berbagai proyek tersebut berdampak pada mobilitas masyarakat, perkembangan kota, penyediaan sandang dan pangan, kesempatan kerja, dan dampak sosial ekonomi lainnya. Aktivitas ilmuwan Belanda pada awalnya berdampak terbatas pada masyarakat kolonial karena sifatnya yang elitis, kurangnya dukungan sosial, hambatan birokrasi, dan keterikatan dalam ranah politik. Ilmuwan Belanda mempunyai posisi penting di berbagai lembaga penelitian, termasuk botani, arkeologi, fisika, dan industri kimia.